A Role of Circulating biomarkers and Maternal-Infant Outcomes after Anticoagulant Therapy In Pregnant Women with Mechanical Heart Valve Replacement: serum TAT, sP-Selectin, NGAL, and PlGF - Shaohui Li, Shaohui Li (Journal of Medical Biochemistry, 2026)
Aim: To investigate the effect of standardized anticoagulation on parturients and fetuses during pregnancy after mechanical heart valve replacement (MHVR) and to evaluate novel serum biomarkers reflecting coagulation activation, endothelial function, placental perfusion, and renal injury. Methods: 100 parturients during pregnancy after MHVR who received treatment in Hebei Xingtai People’s Hospital from January 2019 to December 2024 were recruited and divided into low-molecular-weight heparin (LMWH) group (n=50) and regional citrate anticoagulation (RCA) group (n=50). Coagulation parameters (PT, APTT, TT, FIB, PLT), novel biomarkers (thrombin-antithrombin complex [TAT], soluble P-selectin [sP-selectin], D-dimer), renal biomarkers (urea nitrogen, serum creatinine, neutrophil gelatinase-associated lipocalin [NGAL], asymmetric dimethylarginine [ADMA]), placental and inflammatory markers (placental growth factor [PlGF], interleukin-6 [IL-6]) were compared between groups. Maternal complications and abnormal fetal development were observed. Results: PT and APTT of parturients in RCA group markedly surpassed those in LMWH group, TT was notably inferior to that in LMWH group; FIB decreased more and PLT increased more in RCA group; TAT, sP-selectin, and D-dimer levels were significantly lower in RCA group (P<0.05). After anticoagulant therapy, urea nitrogen and serum creatinine of parturients in RCA group decreased more than those in LMWH group; NGAL and ADMA levels demonstrated greater reduction in RCA group (P<0.05). PlGF levels were significantly higher and IL-6 levels were significantly lower in RCA group (P<0.05). The incidence of various complications in parturients with MHVR in RCA group was obviously inferior to that in parturients with LMWH group (22% vs. 48%, P<0.05), and the incidence of gastrointestinal bleeding was the highest in parturients after MHVR. The probability of fetal dysplasia in LMWH group drastically surpassed that in RCA group (18% vs. 8%, P<0.05). Conclusion: RCA has better effect for parturients and fetuses after MHVR, can apparently improve coagulation indicators and renal function, reduce maternal complications and fetal dysplasia. Novel biomarker profiles indicate that RCA reduces thrombin generation, platelet activation, endothelial injury, and systemic inflammation, while enhancing placental angiogenesis. RCA demonstrates high safety and is worthy of wide clinical application.